Delayed Insemination of Non-Estrual Beef Heifers in 7-day CO-Synch Timed Artificial Insemination - D. C. Shaw; K. E. Fike; David Grieger (Kansas Agricultural Experiment Station Research Reports, 2016)
Reproductive performance in cattle is considered to be the most economically important trait and is essential for the success of an operation. In the last decade, timed artificial insemination (AI) in the beef cattle industry has increased in popularity due to the decreased amount of labor required for estrous detection. To increase the use of AI; however, cost and time inputs need to be further decreased. The objective of this study was to determine if fertility could be improved in beef heifers that are not expressing estrus before timed AI by delaying insemination.
Keywords: fixed time artificial insemination; delayed insemination; estrus